Heart failure among people with Type 2 diabetes mellitus: real‐world data of 289 954 people from a diabetes database. Issue 8 (27th February 2019) - Stoyanova, D.; Stratmann, B.; Schwandt, A.; Heise, N.; Mühldorfer, S.; Ziegelasch, H.‐J.; Zimmermann, A.; Tschoepe, D.; Holl, R. W.; ,
Abstract: Aim: Comparing people with Type 2 diabetes mellitus with and without heart failure in terms of metabolic control, therapeutic regimen and comorbidities. Methods: The Prospective Diabetes Registry (DPV) is a longitudinal documentation system for demographics, medical care and outcome in people with diabetes mellitus. It consists of follow‐up data from people with diabetes mellitus who have agreed to be recorded in the registry. Clinical data are submitted by general practitioners, specialists and clinics throughout Germany and Austria. Some 289 954 people with Type 2 diabetes mellitus (years 2000 to 2015) were analysed using demographic statistics and adjustment for confounders based on linear and logistic regression analysis. Results: People with Type 2 diabetes mellitus (ICD code: E11) and heart failure (ICD code: I50) ( N = 14 723) were older, more often women and presented with longer diabetes duration compared with those without heart failure. After adjustment for age, gender and diabetes duration, people with heart failure showed lower HbA1c, higher BMI and more intense insulin therapy. Analysis revealed that people with heart failure were more often treated with insulin, and more frequently received anti‐hypertensives and lipid‐lowering medication. They presented with lower systolic and diastolic BP. People with heart failure more frequently showed a history of comorbidities. Conclusion: Heart failure is common in diabetes mellitus, but the prevalence in the DPV is lower frequent than expected. The reason for improved metabolic control in heart failure may be intensified therapy with insulin, lipid‐lowering medication and anti‐hypertensives in this cohort. What's new?: Heart failure is a common comorbidity of diabetes mellitus. Prevalence data from intervention studies do not represent real‐world data because the people in studies are often pre‐specified with relation to several underlying diseases. For Germany, data on heart failure prevalence among people with Type 2 diabetes mellitus from large representative cohorts are currently unavailable. Data on diabetes treatment and therapeutic regimens regarding other comorbidities in people with Type 2 diabetes and heart failure are rare. The Prospective Diabetes Registry (DPV) delivers data from nearly 290 000 people with Type 2 diabetes in specialized diabetes care and thus represents real‐world data. The DPV provides data on clinical situation, diabetes treatment and therapeutic regimens regarding other comorbidities in people with Type 2 diabetes and heart failure from all over Germany. The DPV is commonly used to document the real‐world treatment of people with diabetes and either heart failure or other comorbidities. The DPV clearly shows insufficient treatment of dyslipidaemia in people with diabetes and heart failure.